The business strategy partner: culture of innovation - Torres Leandro, Jack D. (Empresa y Sociedad, 2024)
The purpose of this text is to present a bibliographic review of the evolution of the concept of the culture of innovation in the last 37 years, understanding that organizations as such must respond and evolve to the changes that the environment presents. In the era of globalization and economic competitiveness among nations, the importance of innovation to create sustainable economic development and competitive advantage has been intensifying, hand in hand with technological progress that leads the life cycle of the product. One of the factors that influence innovation is culture; being recognized as a factor in management and organizational development, due to its relevance and contribution to the achievement of objectives in the short, medium and long term.